2022
DOI: 10.1186/s12913-022-08349-9
|View full text |Cite
|
Sign up to set email alerts
|

Patient satisfaction and its health provider-related determinants in primary health facilities in rural China

Abstract: Background Patient satisfaction is an important outcome measure of health service and is one of the main reasons for the gradual deterioration of doctor–patient relationships in China. This study used the standardized patient (SP) method to explore patient satisfaction and its health provider-related determinants among primary health facilities in rural China. Methods The dataset comprised 1138 clinic cases in 728 rural primary health facilities in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 51 publications
1
12
3
Order By: Relevance
“…In addition to the above, a study conducted by Gao et al [ 13 ] in China, with the participation of 1,138 patients ‎attending 728 PHC centers distributed over 31 counties, reported a satisfaction level of around 68%, ‎which was highly exceeded by our study results. However, with a finding similar to ours, Gao et ‎al.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…In addition to the above, a study conducted by Gao et al [ 13 ] in China, with the participation of 1,138 patients ‎attending 728 PHC centers distributed over 31 counties, reported a satisfaction level of around 68%, ‎which was highly exceeded by our study results. However, with a finding similar to ours, Gao et ‎al.…”
Section: Discussioncontrasting
confidence: 52%
“…In addition to the above, a study conducted by Gao et al [13] in China, with the participation of 1,138 patients attending 728 PHC centers distributed over 31 counties, reported a satisfaction level of around 68%, which was highly exceeded by our study results. However, with a finding similar to ours, Gao et al [13] indicated that patients' satisfaction is significantly correlated with criteria related to healthcare providers, such as professional level, the consultation process, accessibility, and convenience.…”
Section: Discussioncontrasting
confidence: 49%
“…Several factors are related to the utilization of primary healthcare, such as the variety of services, the consultation process, affordability, and convenience. The situation correlates with patient comfort and satisfaction [ 5 ]. Patient satisfaction is the most crucial and is one of the main reasons patients visit primary healthcare [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…All stakeholders, from the government and doctors to community members, need to be aware of primary healthcare’s role and benefits [ 1 ]. Policy policymakers should pursue patient satisfaction in direct healthcare services by improving the quality of medical services, especially in rural areas [ 5 ]. According to the research background, the study analyzes regional differences in primary healthcare utilization in Java Region in Indonesia.…”
Section: Introductionmentioning
confidence: 99%
“…Existing studies have used the SPs method to explore the relationship between consultation length and health care quality. For example, Gao et al (2022) [30] and Goedhuys et al (2001) [31] found that longer consultation time resulted in higher patient satisfaction; Goedhuys et al (2001) [31] indicated longer consultations were also rated higher for the quality of the communication; Epstein et al (2005) [32] also noted patient-centered communication is associated with increased visit length; Banerjee et al (2020) [33] and Wang et al (2022) [4] found that providers who spent more time with patients were significantly more likely to adherence more checklist items of recommended questions and examinations; besides, Wang et al (2022) [4] found providers who consulted longer time with patients were more likely to give a correct diagnosis. In conclusion, the relationship between consultation length and health care quality has been reasonably well established in face-to-face interactions.…”
Section: Introductionmentioning
confidence: 99%